Vegetation–soil dynamics in an alpine desert ecosystem of the Qinghai Lake watershed, northeastern Qinghai–Tibet Plateau - Zhang, Hongwei; Tian, Lihui; Hasi, Eerdun; Zhang, Dengshan; Wu, Wangyang (Frontiers in Environmental Science, 2023)
Different types of dune causing habitat differences, which can affect the growth of vegetation. In turn, water utilized by vegetation leads to differential distribution of soil moisture in different dunes. However, vegetation-soil dynamics in the alpine desert of the Qinghai–Tibet Plateau remain poorly understood. We chose the largest section of desert along the eastern shore of Qinghai Lake as a study area to approve the hypotheses that plant community characteristics and soil physicochemical properties showed differences in different sand-binding communities, as well as soil moisture content based on methods of field investigations and in situ observations. The main results were as follows. (1) Plant community species diversity and herb coverage increased with the stabilization status of dunes; meanwhile, coverage increased with the age of added artificial semi-fixed dunes. (2) Surface deposits were mainly composed of medium sand leading to low organic matter and nutrient content in the study area; this being different from other deserts in the northern China. (3) Soil moisture’ seasonal variation was consistent with rainfall seasonality and lacked significant interannual differences, while its vertical distribution was influenced by precipitation infiltration. (4) Soil crust formed beneath specific species such as leguminous plants in the study area, which should be effective at preventing wind erosion. Our findings will facilitate a mechanistic understanding of plant–soil–water relationships in alpine deserts and provide timely information for screening introduced species for enhancing sand-fixation effectiveness.